2010
DOI: 10.2105/ajph.2009.180646
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Trends in Long-Term Opioid Analgesic Use for Noncancer Pain

Abstract: Objectives We describe age and gender trends in long-term use of prescribed opioids for chronic noncancer pain in 2 large health plans. Methods Age- and gender-standardized incident (beginning in each year) and prevalent (ongoing) opioid use episodes were estimated with automated health care data from 1997 to 2005. Profiles of opioid use in 2005 by age and gender were also compared. Results From 1997 to 2005, age–gender groups exhibited a total percentage increase ranging from 16% to 87% for incident long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
246
6
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(299 citation statements)
references
References 32 publications
39
246
6
8
Order By: Relevance
“…While not all prevalent prescribing in our study constitutes long-term use, as defined elsewhere, 24 Edlund et al 22 found that the majority of veterans with chronic noncancer pain receiving opioids had over 90 days prescribed per year. Rates of long-term opioid use in two large health plans increased substantially from 1997 to 2005, 25 suggesting that trends outside VHA parallel our observations. The reasons for both the increase and the regional variation in prevalent opioid receipt are unclear.…”
Section: Discussionsupporting
confidence: 78%
“…While not all prevalent prescribing in our study constitutes long-term use, as defined elsewhere, 24 Edlund et al 22 found that the majority of veterans with chronic noncancer pain receiving opioids had over 90 days prescribed per year. Rates of long-term opioid use in two large health plans increased substantially from 1997 to 2005, 25 suggesting that trends outside VHA parallel our observations. The reasons for both the increase and the regional variation in prevalent opioid receipt are unclear.…”
Section: Discussionsupporting
confidence: 78%
“…This definition is similar to that used in the CONSORT study of long-term opioid users. 18,19 Using this definition of long-term use of opioids, some episodes could have been for continuous use whereas others could have been for sporadic or intermittent use. We therefore categorized episodes of long-term opioid use into four groups based on the frequency of drug use.…”
Section: Definitions Of Key Variablesmentioning
confidence: 99%
“…Opioid use may be related to RA or comorbidities; increasing use reflects national trends. 19 We cannot comment on whether this increase was appropriate because we did not analyze patient-level data on the indication for opioid use. Optimal use of opioids remains an area for intervention.…”
Section: Discussionmentioning
confidence: 99%